Production, Redistribution, and Inequality - Alexey V. Zakharov; Vladimir E. Zakharov (Моделирование и анализ информационных систем, 2017)
We use an infinite-dimensional Lotka–Volterra model to analyze production, accumulation, and redistribution of wealth in an economy. We show that, if the amount of wealth produced in the economy is small relative to the amount redistributed, the eventual distribution of wealth will be extremely unequal, with all of it being concentrated in single hands in the limit case. The winner’s identity is determined by his ability to redistribute and produce wealth. Similar outcomes are observed in some physical processes. Article is published in the authors’ wording.